A Dynamic Model Approach of Securitization and the Financial Crisis - Mpundu, Mubanga (International Journal of Economics and Financial Issues, 2016)
Securitization involves the transformation of illiquid assets into liquid and easy to sell ones. The paper focuses on the effect of unexpected negative shocks on Low Quality-asset price and input, Collateralized Debt Obligation price and output as well as profit through the use of numerical analysis. In this regard, two kinds of multiplier processes are considered with the first being the within-period or static multiplier process where the shock such as a ratings downgrade was found to cause a fall in net value of the Low Quality-entity and compels it to reduce its asset demand. In this case, by keeping the future constant, the transaction fees decrease to clear the market and the asset price falls by the same amount. In turn, this lowers the value of the Low Quality-entity's existing assets and reduces their net value even more. Since the future is not constant, this multiplier misses the intuition which was given by the more realistic inter-temporal dynamic multiplier. In this case, the decrease in asset prices results from the cumulative decrease in present and future opportunity costs, stemming from the persistent reductions in the constrained Low Quality-entity's net value and asset demand, which are in turn propelled by a decrease in asset price. The article in addition gives a simulation results for the full nonlinear model taking into consideration the role of uncollateralized asset backed securities. It's clear in the paper that most banks securitize assets without having sufficient capital and liquidity. Keywords: Assets; Credit; Derivatives; Dynamic; Static; Credit Risk. JEL Classifications: G1; E44; C6